1989
DOI: 10.1038/bjc.1989.117
|View full text |Cite
|
Sign up to set email alerts
|

Duration of chemotherapy in small cell lung cancer: a Cancer Research Campaign trial

Abstract: Summary A total of 610 patients with small cell lung cancer were entered into a randomised trial designed to assess the effect of duration of initial chemotherapy on survival. Patients were randomised to receive either four or eight courses of cytotoxic chemotherapy with cyclophosphamide, vincristine and etoposide and also randomised to receive, on disease progression, either second line chemotherapy ( Stopping chemotherapy early may improve the quality of life of the patients by minimising toxicity, but in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
50
0
2

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(56 citation statements)
references
References 8 publications
4
50
0
2
Order By: Relevance
“…This is in keeping with findings from a number of randomized trials that investigated duration of chemotherapy (Cullen et al, 1986;Medical Research Council Lung Cancer Working Party, 1989, 1993Spiro et al, 1989;Giaconne et al, 1993).…”
Section: Discussionsupporting
confidence: 79%
“…This is in keeping with findings from a number of randomized trials that investigated duration of chemotherapy (Cullen et al, 1986;Medical Research Council Lung Cancer Working Party, 1989, 1993Spiro et al, 1989;Giaconne et al, 1993).…”
Section: Discussionsupporting
confidence: 79%
“…5 In general, second-line chemotherapy is considered for cases with recurrent SCLC, and a few studies have reported on the efficacy of some second-line treatments. 6,7 For example, a prospective randomized trial comparing oral topotecan with best supportive care (BSC) revealed the benefits of treatment with oral topotecan in terms of the survival and quality of life. 7 Although some studies have shown the importance of both response and the duration of the response to initial chemotherapy in predicting the efficacy of second-line chemotherapy, [8][9][10] the number of studies conducted to identify the prognostic factors in recurrent SCLC patients is quite limited.…”
Section: Resultsmentioning
confidence: 99%
“…Chemotherapy response rates of greater than 80% are obtained in previously untreated patients (Klastersky et al, 1982;Aisner et al, 1986;Feld et al, 1987;Smith et al, 1987;Jackson et al, 1988;Spiro et al, 1989), and chemotherapy prolongs survival in patients with both limited and extensive disease. Unfortunately these high response rates do not result in significant numbers of cures, and the overall 2-year survival is 5.9%, with 3% alive at 7 years (Souhami & Law, 1990).…”
mentioning
confidence: 99%
“…Chemotherapy relieves symptoms and increases median survival even in patients who cannot be cured, but these benefits have to be weighed against the toxicity and inconvenience of treatment. In the course of a study designed to assess the optimum duration of chemotherapy (Spiro et al, 1989), a quality of life analysis suggested that symptoms improved if chemotherapy was stopped early (Geddes et al, 1990). …”
mentioning
confidence: 99%